2010
DOI: 10.1016/j.cbi.2010.05.015
|View full text |Cite
|
Sign up to set email alerts
|

1-Benzyl-indole-3-carbinol is a novel indole-3-carbinol derivative with significantly enhanced potency of anti-proliferative and anti-estrogenic properties in human breast cancer cells

Abstract: Indole-3-carbinol (I3C), a natural autolysis product of a gluccosinolate present in Brassica vegetables such as broccoli and cabbage, has anti-proliferative and anti-estrogenic activities in human breast cancer cells. A new and significantly more potent I3C analogue, 1-benzyl-I3C was synthesized, and in comparison to I3C, this novel derivative displayed an approximate 1000-fold enhanced potency in suppressing the growth of both estrogen responsive (MCF-7) and estrogen independent (MDA-MB-231) human breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 41 publications
0
19
0
2
Order By: Relevance
“…There is a literature precedent for the reactivity of I3C under acidic conditions, and this appears to translate to the benzylic analogs (Nguyen et al, 2010). We found that the compounds were stable in buffered aqueous environments.…”
Section: Sult1a1 Activates N-bicsmentioning
confidence: 88%
See 2 more Smart Citations
“…There is a literature precedent for the reactivity of I3C under acidic conditions, and this appears to translate to the benzylic analogs (Nguyen et al, 2010). We found that the compounds were stable in buffered aqueous environments.…”
Section: Sult1a1 Activates N-bicsmentioning
confidence: 88%
“…Nguyen et al (2010) identified an N-benzyl derivative of I3C, which is a more potent analog of I3C in killing estrogenresponsive (MCF-7) and estrogen-independent (MDA-MB-231) human breast cancer cells. They further suggested that the parent and analogs are elastase inhibitors that disrupt cyclin E protein processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatin immunoprecipitations were performed as previously described [26,27]. Briefly, cross-linking of proteins to DNA was obtained by the addition of formaldehyde at 1% of the final concentration for 5 min at room temperature to cultured cells.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%
“…It has been shown to sensitize breast cancer cells to tomoxifen, a chemotherapeutic drug used to treat breast cancer [21]. It also has been shown to inhibit bone metastasis of MDA-MB-231 breast cancer cells, in a mouse model [22].…”
Section: Indole-3-carbinolmentioning
confidence: 99%